Development of an opto-electronic fiber device with multiple nano-probes. (29th September 2016) - Mehta, N; Cocking, A; Zhang, C; Ma, D; Xu, Y; Liu, Z
Abstract: We present the fabrication and characterization of an opto-electronic fiber device which can allow for both electromechanical functionality and optical waveguiding capability. The air holes of a photonic crystal fiber are selectively sealed and then pumped with molten metal under pressure. The metal filled holes act as electrodes to which individual carbon nanotubes (CNT) are attached precisely by a laser-welding technique or a focused ion beam assisted pick-and-bond technique. The optical modal profile and the group velocity dispersion of the fabricated device are studied both numerically and experimentally. We also present preliminary experimental proof showing the feasibility of electric actuation of a pair of nanotubes by applying up to 40 V potential difference between the filled electrodes. Furthermore, numerical simulations are carried out which agree with the experimentally observed displacement of the CNT upon electric actuation. The unique aspect of our device is that it provides optical waveguiding and electromechanical nano-probing capability in a single package. Such combined functionality can potentially enable simultaneous electrical and optical manipulation and interrogation at the nanoscale.